2020
DOI: 10.48550/arxiv.2009.05141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Finding hidden order in spin models with persistent homology

Bart Olsthoorn,
Johan Hellsvik,
Alexander V. Balatsky

Abstract: Persistent homology (PH) is a relatively new field in applied mathematics that studies the components and shapes of discrete data. In this work, we demonstrate that PH can be used as a universal framework to identify phases in spin models, including hidden order such as spin nematic ordering and spin liquids. By converting a small number of spin configurations to barcodes we obtain a descriptive picture of configuration space. Using dimensionality reduction to reduce the barcode space to color space leads to a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…[25] for recent interesting criteria for the classification of the confinement-deconfinement crossover. The persistent homology is recently applied to the condensed matter physics and then it has been reported that the hidden order such as spin nematic ordering and spin liquids can be clarified from the persistent homology analysis [26]. Therefore, it seems to be interesting that we can utilize the information theoretic quantity to investigate the mysterious confinement-deconfinement nature of QCD.…”
Section: Introductionmentioning
confidence: 99%
“…[25] for recent interesting criteria for the classification of the confinement-deconfinement crossover. The persistent homology is recently applied to the condensed matter physics and then it has been reported that the hidden order such as spin nematic ordering and spin liquids can be clarified from the persistent homology analysis [26]. Therefore, it seems to be interesting that we can utilize the information theoretic quantity to investigate the mysterious confinement-deconfinement nature of QCD.…”
Section: Introductionmentioning
confidence: 99%